Prenatal exposure to testosterone masculinises the female gerbil and promotes the development of lesions in the prostate (Skene - Biancardi, Manoel Francisco; Perez, Ana Paula da Silva; Caires, Cássia Regina Suzuki [UNESP]; Goes, Rejane Maira [UNESP]; Vilamaior, Patricia Simone Leite [UNESP]; Santos, Fernanda Cristina Alcântara dos; Taboga, Sebastiao Roberto [UNESP] (CSIRO Publishing, 2014)
Androgenic imbalance may disrupt prostate development, leading to morphological alterations in adulthood and predisposing this gland to develop diseases during ageing. However, little is known about the endocrine disruption of the prostate that is caused by androgenic compounds, especially in female experimental models. Therefore, this study aimed to evaluate the prostates of aged female gerbils exposed to testosterone at certain periods in intrauterine and postnatal life, to determine whether exposure at a particular age increases susceptibility to prostatic lesions in these animals. To this end, morphological, stereological, immunohistochemical and immunofluorescence analyses were employed. It was found that females exposed to testosterone during intrauterine life were masculinised, showing increased anogenital distance, absence of the vaginal opening and ectopic development of prostatic tissue. Several areas of adenomatous hyperplasia, generally associated with inflammatory foci and mainly located in the ectopic prostatic tissue around the vaginal wall, were also observed. In conclusion, the results showed that abnormal prenatal exposure to testosterone severely affects the reproductive systems of female animals by disrupting normal prostate morphogenesis and increasing susceptibility to the development of prostatic diseases during ageing.
Keywords: androgens; endocrine-disrupting chemicals